Occupational accidents and musculoskeletal disorders in Greek Armed Forces in Evros county - Malliarou, Maria; Karathanasi, Konstantinia; Moustaka, Heleni; Sotiriadou, Kiriaki; Constantinidis, Theodoros; Sarafis, Pavlos (My University, 2012)
The purpose of this study was to investigate musculoskeletal disorders in Greece in relation to occupational accidents of army personnel in Evros County.
Keywords: Musculoskeletal disorders; Greek army; Army personnel; Evros